Pemberdayaan Perempuan melalui Pendidikan Islam Progresif Suud Sarim Karimullah: Analisis Strukturalisme dan Implikasinya - Sugitanata, Arif; Hasan, Faradila; Kurniawan, M. Rafli; Aminah, Siti (Pusat Studi Gender dan Anak Universitas Islam Negeri Antasari Banjarmasin, 2024)
This study aims to explore the role of Progressive Islamic Education in women's empowerment from the perspective of Suud Sarim Karimullah. It employs a qualitative research methodology, focusing on a literature review that includes an analysis of the works of Suud Sarim Karimullah and related literature, such as relevant books and journals, analyzed based on structuralism theory. This study demonstrates that Progressive Islamic Education, which combines fundamental Islamic principles with modern values such as gender equality and human rights, can enhance women's access to quality education. This education not only empowers women in terms of education but also increases their participation in the workforce and political decision-making. Additionally, Progressive Islamic Education helps to overcome social and cultural barriers, as well as gender stereotypes that limit women's roles. By involving the Muslim community, including religious leaders and families, Progressive Islamic Education can foster positive change in society. The impact of women's empowerment through Progressive Islamic Education is evident in the improvement of economic well-being, poverty reduction, and increased social stability. Structuralism analysis shows that Progressive Islamic Education can shape social structures that support change, address patriarchal norms, and promote sustainable gender equality. Therefore, from the perspective of Suud Sarim Karimullah, Progressive Islamic Education is an effective tool for women's empowerment and the development of an inclusive and just society.